On the Preparation of the Initial Data For Prognostic Problem of the Baroclinic Ocean Dynamics - Kordzadze, Avtandil A. (Journals of Georgian Geophysical Society, 2017)
It is well known that quality of the hydrophysical fields received as a result of realization of the prognostic model of the dynamics of the baroclinic ocean considerably depends on quality of the input data. In the present study, on the basis of the conjugated equations and the perturbation theory the algorithm for specification of the observational data on the non-stationary processes, used in the boundary conditions on the free sea surface, is offered. With the purpose of convenience, at first the algorithm on preparation of the initial data for the prognostic model of the ocean dynamics is considered on an example of two-dimensional, xoz-coordinate plane, transfer-diffusion equation for a substance, and then - for a three-dimensional problem of dynamics of baroclinic ocean.